دعا ونيايش معبود در شعر سبک عراقی - التميمي، خالد حفظي عبدالأمير (كلية العلوم الإنسانية والاجتماعية, 2021)
Iranian poets and writers from ancient times began their poems and writings in the name of God Almighty because they have taken the hadith of the Prophet (PBUH): "Every matter of concern in which he did not begin in the name of God is justified", as a method for their literary works. Praise be to these poets and writers, the greatness and quality of God, and they resorted to Him, humbled and humbled. In this praiseworthy way, the best beginning for all writings and poems is the salvation with God, and a treasure of wisdom and knowledge was not opened unless his key was to describe the unification of the Almighty. The different roles of Persian literature were called with different names. From the seventh to the ninth century AH, a style in Persian literature matured and continued for two centuries, and was popular in Iraq AlAjam, ie Isfahan and other areas of Iran, mostly. Nizami Kanjoi is one of the glorious poets of this method. He is the owner of the unique effect "Bing King" (The Five Treasures), which was followed by many poets in singing their poems. In this effect, from the beginning to the end, especially at the beginning of all the two commons, two systems devoted many chapters to God's praise and salvation with him. Credits in all literary monuments form part of the literary texts. Paying attention to the price of this Najwa in terms of both content and content led to the conduct of this research whose purpose is to study the sections of Najwa (its content and implications), the Najwa in the Holy Qur’an, as well as the Iraqi poetry style and the most prominent poets of this method any system and study the types of Najwa and supplication in his literature.
بدأ الشعراء والكتاب الإيرانيين منذ القدم قصائدهم وكتاباتهم باسمه تعالي لأنهم اتخذوا حديث النبي (صلى الله عليه وسلم): "كل أمر ذي بال لم يبدأ فيه باسم الله فهو أبتر"، منهجا لأعمالهم الأدبية. فحمد هؤلاء الشعراء والكتاب عظمة الله وجوده ولجأوا إليه خاشعين متصدعين. وفق هذه الطريقة المحمودة، البداية الفضلي لجميع الكتابات والقصائد هي النجوى مع الله ولم يفتح كنز من كنوز الحكمة والمعرفة إلا أن يكون مفتاحه وصف توحيده سبحانه وتعالي. سميت أدوار أدب الفارسي المختلفة بأسماء متفاوتة. منذ القرن السابع إلى التاسع الهجري نضج أسلوب في أدب الفارسي وواصل حياته إلى قرنين وكان رائجا في عراق العجم أي أصفهان وسائر نواحي إيران غالبا. نظامي كنجوي أحد الشعراء المجيدين لهذا الأسلوب فهو صاحب الأثر الفريد "بنج كنج" (الكنوز الخمسة) الذي اقتفاه كثير من الشعراء في إنشاد قصائدهم. في هذا الأثر، من ألفه إلى يائه، خاصة في بداية كل مثنوي خصص نظامي أبياتا كثيرة لثناء الله والنجوى معه. تكون التحمديات في الآثار الأدبية كافة، قسما من النصوص الأدبية. الاهتمام بثمن هذه النجوى من حيث الكيفية والفحوى أدى إلى القيام بهذا البحث الذي غايته دراسة أقسام النجوى (فحواها ومضامينها)، النجوى في القرآن الكريم وكذلك أسلوب الشعر العراقي وأبرز شعراء هذا الأسلوب أي نظامي ودراسة أنواع النجوى والدعاء في أدبه.
Keywords: الشعر الفارسي -- الأساليب الشعرية -- الدعاء -- النجوى -- الشعراء الإيرانيون -- كنجوى، نظامي